Accelerated removal of five pesticide residues in three vegetables with ozone microbubbles. (1st March 2023) - Li, Xiaohan; Liu, Chengcheng; Liu, Fengmao; Zhang, Xianzhao; Peng, Qingrong; Wu, Ge; Lin, Jin; Zhao, Zhanping
Graphical abstract: Highlights: Ozone microbubbles significantly improved pesticide removal efficiency. Pesticide residues removal mechanisms include physical and chemical removal. The degradation pathway of emamectin benzoate was explored by MS. The epidermis morphology of vegetables affects the removal efficiency. Changes in vitamin C were negligible under ozone microbubble treatment. Abstract: A simple and effective approach to remove pesticide residues on vegetables is necessary for food safety. Ozone microbubbles treatment as an eco-friendly washing technique was investigated for three vegetables (celery, pakchoi and cowpea) collected from the field applied with five pesticides. The removal rates of five pesticide residues on cowpea by ozone microbubbles treatment were 15 %–47 % higher than that by ozone macrobubbles. Moreover, compared with the other four systemic pesticides, emamectin benzoate had a preferable removal rate (65 %–94 %) as a non-systemic pesticide with high water solubility. Through Mass Spectrometry (MS), the double-bonded structure of emamectin benzoate made it more possible to be removed chemically, carrying a degradation rate of 88 % at 25 min in water. Additionally, cowpea showed low removal (28 %–65 %) owing to its stomata and rough surface with SEM. Conclusively, this study demonstrated the potential of the ozone microbubble treatment on pesticide residues removal to enhance food safety.